Local Government Strategy in Managing Objects Marine Tourism in Banggai Laut District - Sigittriadi; Burhan Niode; Johny P. Lengkong (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
Marine tourism is one of the tourist attractions of Banggai Laut Regency. Marine tourism is a major industry in Banggai Laut Regency, but it is less popular and attracts fewer visitors than other tourist destinations. If you want to draw public interest, there has to be a local government strategy in place to manage maritime tourism. Of course, the tourist business is strongly dependent on public trust. The federal and local governments should strive more to reestablish the tourism business during the pandemic. The goal of this research was to identify and investigate the local government's plan for managing maritime tourist items in Banggai Laut Regency. This study employs a descriptive method with a qualitative approach. According to the conclusions of this study, the Banggai Laut Regency's local administration has not yet optimized its plan for managing maritime tourist items. This is due to the local government's present concentration on other beaches that have been under control for a long time, as well as the importance of pandemic prevention from all angles, including the tourism business. construct amenities and infrastructure, and ensure tourist safety.